Metal Cu (at) ZnOx core-shell structure nano catalyst as well as preparation method and application of metal Cu (at) ZnOx core-shell structure nano catalyst

By using metal Cu@ZnOx core-shell structure nanocatalysts, the Cu-ZnOx interface active site is optimized, the problem of insufficient reactivity of existing catalysts is solved, the methanol generation rate is significantly improved, and it has good industrial application potential.

CN119608171AActive Publication Date: 2025-03-14DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202311159619.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-08
Publication Date
2025-03-14
Estimated Expiration
2043-09-08

AI Technical Summary

Technical Problem

In the existing CuZnAl catalysts, in the hydrogenation of carbon dioxide to methanol, there are fewer Cu-ZnOx interface active sites, resulting in insufficient reaction activity and low generation rate.

Method used

The metal Cu@ZnOx core-shell structure nanocatalyst was used to adjust the thickness of the ZnOx shell by controlling the processing time and optimize the number of Cu-ZnOx interface active sites. The catalyst consists of metal Cu nanoparticles as cores, zinc oxide thin layer as shells, and a support is aluminum oxide.

Benefits of technology

The methanol generation rate of Cu-based catalysts in the methanol generation process of medium and low temperature and low pressure carbon dioxide hydrogenation to methanol is significantly improved, and has high versatility and industrial application potential.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119608171A_ABST
    Figure CN119608171A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of preparation of methanol through hydrogenation of carbon dioxide, in particular to a metal Cu (at) ZnOx core-shell structure nano catalyst as well as a preparation method and application of the metal Cu (at) ZnOx core-shell structure nano catalyst. The catalyst comprises a core-shell structure and a carrier, the core structure is metal Cu nanoparticles, the shell structure is a zinc oxide thin layer, and the carrier is aluminum oxide. The surfaces of the metal Cu nanoparticles of the catalyst are wrapped by ultrathin zinc oxide (ZnOx), the catalyst has a core-shell structure, and the catalyst shows a high methanol generation rate in a reaction for preparing methanol through hydrogenation of carbon dioxide at medium and low temperatures and low pressure. The preparation method of the catalyst is simple and reliable, raw materials are easy to obtain, and the catalyst has universality.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of carbon dioxide hydrogenation to methanol, and in particular to a metal Cu@ZnO x Core-shell structured nanocatalyst, preparation method and application thereof. Background Art

[0002] With the rapid growth of global energy demand and the massive consumption of fossil energy, a large amount of carbon dioxide (CO2) emissions are generated. Global climate change caused by carbon dioxide as a greenhouse gas has become a serious global concern. Converting CO2 into valuable chemicals is an ideal way to alleviate this problem. CO2 molecules are thermodynamically stable, and if CO2 is only a single reactant, a lot of energy will be required. However, if another substance with a higher Gibbs free energy is introduced as a co-reactant (such as H2), it becomes thermodynamically easier. Therefore, the use of CO2 hydrogenation to prepare high-value chemicals such as oxygen-containing compounds (alcohols and dimethyl ether), hydrocarbons (olefins, liquid hydrocarbons and aromatics) is one of the most promising conversion and utilization pathways.

[0003] Methanol (CH3OH) is an important chemical raw material that can be used as a fuel for internal combustion engines and fuel cells. With the depletion of non-renewable energy sources, methanol is also an alternative raw material for the production of chemicals and even gasoline. Nowadays, with the successful development of active catalysts (zeolite-based catalysts), processes such as methanol to olefins (MTO) and methanol to propylene (MTP) have attracted great attention. The market demand for methanol-derived fuels has increased significantly from 6% in 2011 to 22% in 2016. Therefore, CO2 conversion to methanol is one of the most attractive pathways for CO2 utilization conversion.

[0004] Among the various catalysts for hydrogenation of carbon dioxide to methanol developed so far, such as Cu-based catalysts, supported noble metal catalysts and other types of catalysts, CuZnAl catalysts are still one of the catalysts that have received the most research attention and have the best industrial prospects due to their relatively low cost and good reaction activity. In CuZnAl catalysts prepared by traditional methods (such as coprecipitation method), only part of the ZnO particles have interface contact with the CuO particles, resulting in Cu-ZnAl x There are few active sites on the interface, and the reaction activity still has room for improvement. Therefore, it is very important to study new catalyst preparation methods to optimize the interface structure of CuZnAl catalysts and thus increase the rate of production of methanol by hydrogenation of carbon dioxide.

[0005] In order to improve the methanol production rate of Cu-based catalysts, researchers have done a lot of work. On the one hand, the activity of methanol production is improved by adding additives (such as alkali metals, alkaline earth metals, and rare earth metals). For example, the doping of cerium oxide can promote the combination between Cu and CO, making it difficult for CO to desorb from the surface, thereby inhibiting the reverse water gas exchange reaction and the decomposition of methanol, and selectively promoting the synthesis of methanol. On the other hand, suitable carrier materials (such as zirconium oxide and cerium oxide) can be selected to adjust the surface pH of the catalyst and the electronic state of Cu to affect the adsorption and activation of CO2 and H2, thereby promoting the methanol synthesis performance of Cu-based catalysts. In addition, oxides (such as SiO2) can be covered on the surface of metal nanoparticles to form a core-shell structure, which can effectively prevent the growth and aggregation of metal particles, and its good metal dispersion can improve the catalytic performance. However, these methods have relatively high raw material costs, or the preparation process is relatively complicated, and it is difficult to achieve large-scale preparation of catalysts, so it is not conducive to the promotion of industrial applications. Summary of the invention

[0006] The purpose of the present invention is to provide a metal Cu@ZnO x Core-shell structure nanocatalyst and its preparation method and application. The preparation method is simple and reliable and can be used for low-temperature and low-pressure carbon dioxide hydrogenation to methanol reaction. The nano core-shell structure of the catalyst can provide more Cu-ZnO x interfacial active sites, thereby improving the methanol production rate of Cu-based catalysts.

[0007] In order to achieve the above object, the technical solution of the present invention is as follows:

[0008] The present invention provides a metal Cu@ZnO x A nanocatalyst with a core-shell structure, the catalyst comprising a core-shell structure and a carrier: the core structure is a metal Cu nanoparticle, the shell structure is a zinc oxide thin layer, and the carrier is aluminum oxide, denoted as Cu@ZnO x / Al2O3.

[0009] In the above technical solution, further, the catalyst particle size is directly related to the metal Cu loading, and the loading is mass loading, which is calculated as metal mass / total catalyst mass; the particle size of the metal Cu nanoparticles is 5-50nm, and the metal Cu nanoparticles account for 4-90% of the total catalyst mass in terms of mass fraction.

[0010] In the above technical solution, further, the zinc oxide composition is recorded as ZnO x The thickness is controllable and at the nanoscale, with a thickness within 1nm.

[0011] In the above technical solution, further, the alumina carrier is amorphous alumina or γ-type alumina.

[0012] Another aspect of the present invention provides a method for preparing the above core-shell structured nanocatalyst, the method comprising the following steps:

[0013] (1) dissolving a metallic copper precursor and a metallic aluminum precursor in water at a copper-aluminum molar ratio of 0.03-8.50:1, stirring evenly to obtain a mixed solution, adding the mixed solution dropwise into a stirred sodium carbonate solution at 65° C., washing the obtained precipitate with deionized water, and drying the obtained powder, treating the obtained powder at 500° C. in a pure H2 atmosphere for 2-4 h at a flow rate of 50-100 ml / min, to obtain a Cu / Al2O3 sample;

[0014] (2) The Cu / Al2O3 sample obtained in step (1) is separated from the zinc source solid powder by quartz wool, placed in a quartz reaction tube with the zinc source at the front end and the Cu / Al2O3 sample at the rear end, and treated in a carbon dioxide hydrogenation atmosphere at 450° C. for 1-200 h to obtain the core-shell structure catalyst.

[0015] In the above technical solution, further, in step (1), the metallic copper precursor is at least one of copper nitrate, chlorate, acetate and sulfate;

[0016] The metal aluminum precursor is at least one of aluminum nitrate, aluminum chlorate and aluminum sulfate.

[0017] In the above technical solution, further, in step (1), the drying temperature is 110° C. and the drying time is 12-24 hours.

[0018] In the above technical solution, further, in step (2), the zinc source is at least one of zinc oxide and metallic zinc.

[0019] In the above technical solution, further, in step (2), the separation distance between the Cu / Al2O3 sample and the zinc source is 2mm-1cm.

[0020] In the above technical solution, further, in step (2), the thickness of the shell layer is adjusted by changing the treatment time during the preparation process. The longer the time, the thicker the shell layer. The treatment time is preferably 100-150 hours.

[0021] In the above technical solution, further, the carbon dioxide hydrogenation atmosphere is a mixed gas containing inert gas with a volume ratio of carbon dioxide to hydrogen of 1 / 199-1 / 3; the inert gas is at least one of high-purity Ar and high-purity N2.

[0022] In another aspect, the present invention provides an application of the core-shell structured nanocatalyst in the hydrogenation of carbon dioxide to produce methanol, wherein the reaction conditions are: pressure 2-4 MPa, reaction gas flow rate 20-100 mL / min, and reaction temperature 200-260°C.

[0023] The beneficial effects of the present invention are:

[0024] 1. The surface of the catalyst metal Cu nanoparticles of the present invention is covered with ultra-thin zinc oxide (ZnO x ) is wrapped, having a core-shell structure, and the core-shell structure can be controlled by controlling the processing time. x The shell thickness can be precisely controlled x The number of active sites at the contact interface is optimized. Therefore, the catalyst exhibits a high methanol product formation rate in the reaction of carbon dioxide hydrogenation to methanol at medium-low temperature and low pressure.

[0025] 2. The preparation method of the present invention has a simple process, cheap raw materials, strong versatility, and great application potential. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The X-ray diffraction pattern and transmission electron microscope image of the sample in Example 1, a is the X-ray diffraction pattern, and b is the transmission electron microscope image;

[0027] Figure 2 The dark field high resolution scanning transmission electron microscopy image and the energy spectrum element distribution map of the sample in Example 1, a is a dark field high resolution scanning transmission electron microscopy image, and b is an energy spectrum element distribution map;

[0028] Figure 3 are the X-ray excited Auger spectra of the sample in Example 1, a is the Zn LMM Auger spectrum, and b is the Cu LMM Auger spectrum;

[0029] Figure 4 The dark field high resolution scanning transmission electron microscopy image and the energy spectrum element distribution map of the sample in Example 4, a is a dark field high resolution scanning transmission electron microscopy image, and b is an energy spectrum element distribution map;

[0030] Figure 5 This is a test graph of the methanol production rate of the product of the carbon dioxide hydrogenation reaction of the sample in Example 5 and the commercial CuZnAl catalyst;

[0031] Figure 6 This is a stability test diagram of the sample in Example 5 and the commercial CuZnAl catalyst in the carbon dioxide hydrogenation reaction. DETAILED DESCRIPTION

[0032] The present invention is described in detail below by way of examples, but the scope of the claims of the present invention is not limited by these examples. Meanwhile, the examples only provide partial conditions for achieving this purpose, and do not mean that these conditions must be met to achieve this purpose.

[0033] Example 1

[0034] (1) 25 g of copper nitrate nonahydrate and 6.85 g of aluminum nitrate trihydrate were dissolved in water and stirred to obtain a mixed solution. The mixed solution was added dropwise into a stirred sodium carbonate solution at 65° C. The obtained precipitate was washed with deionized water and dried in an oven at 110° C. for 12-24 h. The powder obtained after drying was treated in pure H2 at 500° C. for 4 h at a flow rate of 80 ml / min to obtain a Cu / Al2O3 sample;

[0035] (2) The aforementioned 0.15 g Cu / Al2O3 sample and 0.3 g zinc oxide particles were separated by quartz wool at a distance of about 3 mm and placed in a quartz reaction tube, with the zinc oxide particles at the front end and the Cu / Al2O3 sample at the rear end. The reaction tube was treated in a 0.5% CO2 / H2 atmosphere at 450°C for 100 h. The Cu / Al2O3 at the rear end was separated to obtain about 69 wt% Cu@ZnO x / Al2O3 core-shell structure catalyst.

[0036] In Example 1, 69wt% Cu@ZnO x / Al2O3 core-shell structure X-ray diffraction spectrum ( Figure 1 a) and transmission electron microscopy ( Figure 1 b) Characterization shows that the Cu particles in the synthesized catalyst are supported on amorphous alumina with a particle size of about 30 nm. High-resolution scanning transmission electron microscopy ( Figure 2 a) and the corresponding element distribution of the energy spectrum ( Figure 2 b) Analysis shows that the surface of Cu nanoparticles is coated with a Zn-containing oxide layer with a thickness of about 1 nm, which is a typical core-shell structure. Quasi-in-situ X-ray excited Auger spectrum shows that the surface of Cu particles is in a reduced state, and the Zn species in the surface coating layer is in an oxidized state ( Figure 3 ).

[0037] Example 2

[0038] (1) 0.1 g of copper nitrate nonahydrate and 5 g of aluminum nitrate trihydrate were dissolved in water, stirred evenly to obtain a mixed solution, and the mixed solution was added dropwise into a stirred 65° C. sodium carbonate solution. The obtained precipitate was washed with deionized water and dried in an oven at 110° C. for 12-24 h. The powder obtained after drying was treated in pure H2 at 500° C. for 4 h at a flow rate of 80 ml / min to obtain a Cu / Al2O3 sample;

[0039] (2) The aforementioned 0.15 g Cu / Al2O3 sample and 0.3 g zinc oxide particles were separated by quartz wool at a distance of about 3 mm and placed in a quartz reaction tube, with the zinc oxide particles at the front end and the Cu / Al2O3 sample at the rear end. The tube was treated in a 0.5% CO2 / H2 atmosphere at 450°C for 100 h. The Cu / Al2O3 at the rear end was separated to obtain about 4 wt% Cu@ZnO x / Al2O3 core-shell structure catalyst. The average size of Cu particles in the catalyst of Example 2 is about 5nm.

[0040] Example 3

[0041] (1) 25 g of copper nitrate nonahydrate and 5 g of aluminum nitrate trihydrate were dissolved in water and stirred to obtain a mixed solution. The mixed solution was added dropwise into a stirred 65° C. sodium carbonate solution. The obtained precipitate was washed with deionized water and dried in an oven at 110° C. for 12-24 h. The powder obtained after drying was treated in pure H2 at 500° C. for 4 h at a flow rate of 80 ml / min to obtain a Cu / Al2O3 sample.

[0042] (2) The aforementioned 0.15 g Cu / Al2O3 sample and 0.3 g zinc oxide particles were separated by quartz wool at a distance of about 3 mm and placed in a quartz reaction tube, with the zinc oxide particles at the front end and the Cu / Al2O3 sample at the rear end. The tube was treated in a 0.5% CO2 / H2 atmosphere at 450°C for 100 h. The Cu / Al2O3 at the rear end was separated to obtain about 90 wt% Cu@ZnO x / Al2O3 core-shell structure catalyst. The average size of Cu particles in the catalyst of Example 3 is about 50nm.

[0043] Example 4

[0044] (1) 25 g of copper nitrate nonahydrate and 6.85 g of aluminum nitrate trihydrate were dissolved in water and stirred to obtain a mixed solution. The mixed solution was added dropwise into a stirred 65° C. sodium carbonate solution. The obtained precipitate was washed with deionized water and dried in an oven at 110° C. for 12-24 h. The powder obtained after drying was treated in pure H2 at 500° C. for 4 h at a flow rate of 80 ml / min to obtain a Cu / Al2O3 sample.

[0045] (2) The aforementioned 0.15 g Cu / Al2O3 sample and 0.3 g zinc oxide particles were separated by quartz wool at a distance of about 3 mm and placed in a quartz reaction tube, with the zinc oxide particles at the front end and the Cu / Al2O3 sample at the rear end. The tube was treated in a 0.5% CO2 / H2 atmosphere at 450°C for 60 h. The Cu / Al2O3 at the rear end was separated to obtain about 87 wt% Cu@ZnO x / Al2O3 core-shell structure catalyst. The Cu particle size in the catalyst of Example 4 is about 30nm.

[0046] Dark-field high-resolution scanning transmission electron microscopy ( Figure 4 a) and the corresponding element distribution of the energy spectrum ( Figure 4 b) Analysis shows that the surface of the Cu nanoparticles is coated with Zn-containing oxides, and the core-shell structure is similar to the sample in Example 1, but the shell thickness is about 0.6 nm. The shell thickness can be controlled by changing the pretreatment conditions.

[0047] Example 5

[0048] (1) 25 g of copper nitrate nonahydrate and 6.85 g of aluminum nitrate trihydrate were dissolved in water and stirred to obtain a mixed solution. The mixed solution was added dropwise into a stirred sodium carbonate solution at 65° C. The obtained precipitate was washed with deionized water and dried in an oven at 110° C. for 12-24 h. The powder obtained after drying was treated in pure H2 at 500° C. for 4 h at a flow rate of 80 ml / min to obtain a Cu / Al2O3 sample;

[0049] (2) The aforementioned 0.15 g Cu / Al2O3 sample and 0.3 g zinc oxide particles were separated by quartz wool at a distance of about 3 mm and placed in a quartz reaction tube, with the zinc oxide particles at the front end and the Cu / Al2O3 sample at the rear end. The reaction tube was treated in a 0.5% CO2 / H2 atmosphere at 450°C for 150 h. The Cu / Al2O3 sample at the rear end was separated to obtain about 67 wt% Cu@ZnO x / Al2O3 core-shell structure catalyst. In the catalyst of Example 5, the Cu particle size is about 30nm, and the shell thickness is about 0.7nm.

[0050] Example 6

[0051] (1) 25 g of copper nitrate nonahydrate and 6.85 g of aluminum nitrate trihydrate were dissolved in water and stirred to obtain a mixed solution. The mixed solution was added dropwise into a stirred sodium carbonate solution at 65° C. The obtained precipitate was washed with deionized water and dried in an oven at 110° C. for 12-24 h. The powder obtained after drying was treated in pure H2 at 500° C. for 4 h at a flow rate of 80 ml / min to obtain a Cu / Al2O3 sample;

[0052] (2) The aforementioned 0.15 g Cu / Al2O3 sample and 0.3 g metal Zn particles were separated by quartz wool at a distance of about 3 mm and placed in a quartz reaction tube, with the metal Zn particles at the front end and the Cu / Al2O3 sample at the rear end. The tube was treated in a 0.5% CO2 / H2 atmosphere at 450°C for 1 h. The separated Cu / Al2O3 sample at the rear end also obtained about 87 wt% Cu@ZnOx / Al2O3 core-shell structure catalyst. The Cu particle size in the catalyst is about 30nm, and the shell thickness is about 0.2nm.

[0053] Example 7

[0054] 1. Weigh 67wt% Cu@ZnO from Example 5 x / Al2O3 catalyst 100mg, loaded into a micro vertical fixed bed quartz tube reactor. Pure hydrogen 20mL / min, pretreated at 250℃ for 2h. Constant temperature at 250℃, cut into carbon dioxide hydrogenation reaction gas (24% CO2 / 72% H2 / 4% N2), pressurized to 3.0MPa, gas flow rate of 20mL / min. The generated product was analyzed online by AgilentGC8890 chromatographic, equipped with HP-INNOWax chromatographic column and thermal conductivity detector, record and calculate the methanol generation rate after 2h of sample reaction (TOF of methanol generation: conversion frequency of methanol generation at a single active site).

[0055] 2. Weigh 100 mg of commercial CuZnAl catalyst (Sichuan Shutai, low-pressure methanol synthesis catalyst SCST-253-55) and load it into a micro vertical fixed bed quartz tube reactor. Pass pure hydrogen at 20 mL / min, pre-treat at 250°C for 2 hours, keep constant at 250°C, switch to carbon dioxide hydrogenation reaction gas (24% CO2 / 72% H2 / 4% N2), increase the pressure to 3.0 MPa, and the gas flow rate is 20 mL / min. The generated product is analyzed online by Agilent GC8890 chromatographic analysis, equipped with HP-INNOWax chromatographic column and thermal conductivity cell detector, and the methanol generation rate after the sample reacts for 2 hours is recorded.

[0056] Figure 5 The 67wt% Cu@ZnO in Example 5 x The results of the evaluation of the methanol production rate of the product of the carbon dioxide hydrogenation reaction using the CuZnAl / Al2O3 catalyst and the commercial CuZnAl catalyst. It can be seen that the methanol conversion frequency of the commercial CuZnAl catalyst is 102.8h-1, while the 67wt% Cu@ZnO x The methanol production rate of the / Al2O3 catalyst is 123.1h -1 , and its performance is better than that of commercial CuZnAl catalyst. The above results show that Cu@ZnO x / Al2O3 core-shell structure catalyst can be used as an excellent catalyst for the hydrogenation of carbon dioxide to methanol reaction and has potential industrial application value.

[0057] Example 8

[0058] 1. Weigh 67wt% Cu@ZnO from Example 5 x / Al2O3 catalyst 100mg, loaded into a micro vertical fixed bed quartz tube reactor. Pure hydrogen 20mL / min, pretreated at 250℃ for 2h. Constant temperature at 250℃, cut to carbon dioxide hydrogenation reaction gas (24% CO2 / 72% H2 / 4% N2), increase the pressure to 3.0MPa, gas flow rate of 20mL / min. The generated product was analyzed online by AgilentGC8890 chromatographic, equipped with HP-INNOWax chromatographic column and thermal conductivity detector, the sample was reacted for 30h, and the change of methanol generation rate was monitored.

[0059] 2. Weigh 100 mg of commercial CuZnAl catalyst (Sichuan Shutai, low-pressure methanol synthesis catalyst SCST-253-55) and load it into a micro vertical fixed bed quartz tube reactor. Pass pure hydrogen at 20 mL / min and pretreat at 250°C for 2 hours. Keep the temperature at 250°C, switch to carbon dioxide hydrogenation reaction gas (24% CO2 / 72% H2 / 4% N2), increase the pressure to 3.0 MPa, and the gas flow rate is 20 mL / min. The generated product is analyzed online by Agilent GC8890 chromatography, equipped with HP-INNOWax chromatographic column and thermal conductivity cell detector. The sample reacts for 30 hours and monitors the change in methanol generation rate.

[0060] Figure 6 The 67wt% Cu@ZnO in Example 5 x / Al2O3 catalyst and commercial CuZnAl catalyst for carbon dioxide hydrogenation reaction stability evaluation results. It can be seen that after 30 hours of testing, 67wt% Cu@ZnO x / Al2O3 catalyst and commercial CuZnAl catalyst have comparable stability.

[0061] In summary, the beneficial effects of the present invention are: direct synthesis of metal Cu@ZnO x Core-shell nanocatalysts improve the shortcomings of previous core-shell materials, which require a lot of raw materials and cannot controllably modify metal nanoparticles at the nanoscale. They have good versatility. In addition, Cu@ZnO is used as a catalyst in the low-temperature and low-pressure carbon dioxide hydrogenation reaction to produce methanol. x Core-shell structure with optimal Cu-ZnO x The number of interfacial active sites can significantly increase the methanol production rate of the carbon dioxide hydrogenation reaction of Cu-based catalysts, and has great application potential.

[0062] The above embodiments are only preferred embodiments of the present invention and are not intended to limit the implementation methods. The protection scope of the present invention shall be subject to the scope defined in the claims. Other different forms of changes or modifications may be made based on the above description. Obvious changes or modifications derived therefrom are still within the protection scope of the present invention.

Claims

1. A metal Cu@ZnO x The core-shell structured nanocatalyst is characterized by: The catalyst comprises a core-shell structure and a carrier: the core structure is metal Cu nanoparticles, the shell structure is a zinc oxide thin layer, and the carrier is aluminum oxide.

2. The catalyst according to claim 1, characterized in that: The particle size of the metal Cu nanoparticles is 5nm-50nm, and the metal Cu nanoparticles account for 4%-90% of the mass of the entire catalyst in terms of mass fraction; The thickness of the zinc oxide thin layer is within 1 nm.

3. The catalyst according to claim 1, characterized in that: The alumina carrier is amorphous alumina or gamma alumina.

4. The method for preparing a core-shell structured nanocatalyst according to any one of claims 1 to 3, characterized in that: The method comprises the following steps: (1) dissolving a metallic copper precursor and a metallic aluminum precursor in water at a copper-aluminum molar ratio of 0.03-8.50:1, stirring evenly to obtain a mixed solution, adding the mixed solution dropwise into a stirred sodium carbonate solution at 65° C., washing the obtained precipitate with deionized water, and drying the obtained powder, treating the obtained powder at 500° C. in a pure H2 atmosphere for 2-4 h at a flow rate of 50-100 ml / min, to obtain a Cu / Al2O3 sample; (2) The Cu / Al2O3 sample obtained in step (1) is separated from the zinc source solid powder by quartz wool, placed in a quartz reaction tube with the zinc source at the front end and the Cu / Al2O3 sample at the rear end, and treated in a carbon dioxide hydrogenation atmosphere at 450° C. for 1-200 h to obtain the core-shell structure catalyst.

5. The preparation method according to claim 4, characterized in that: In step (1), the metallic copper precursor is at least one of copper nitrate, chlorate, acetate and sulfate; The metal aluminum precursor is at least one of aluminum nitrate, aluminum chlorate and aluminum sulfate.

6. The preparation method according to claim 4, characterized in that: In step (1), the drying temperature is 110° C. and the drying time is 12-24 hours.

7. The preparation method according to claim 4, characterized in that: In step (2), the zinc source is at least one of zinc oxide and metallic zinc.

8. The preparation method according to claim 4, characterized in that: In step (2), the separation distance between the Cu / Al2O3 sample and the zinc source is 2 mm-1 cm.

9. The preparation method according to claim 4, characterized in that: The carbon dioxide hydrogenation atmosphere is a mixed gas containing an inert gas with a volume ratio of carbon dioxide to hydrogen of 1 / 199-1 / 3; the inert gas is at least one of high-purity Ar and high-purity N2.

10. Use of the core-shell structured nanocatalyst according to any one of claims 1 to 3 in the hydrogenation of carbon dioxide to methanol, characterized in that: The reaction conditions are: pressure 2-4 MPa, reaction gas flow rate 20-100 mL / min, reaction temperature 200-260°C.

Citation Information

Patent Citations

  • Copper nickel-zinc oxide composite nanocrystalline photocatalyst and preparation method and application thereof

    CN105664951A

  • Core-shell structural catalyst for preparing methanol by carbon dioxide hydrogenation and preparation method of core-shell structural catalyst

    CN109364931A

  • Preparation method of heatproof copper-zinc based catalyst

    CN109420502A

  • Catalyst for preparing methanol through hydrogenation of carbon dioxide and preparation method and application thereof

    CN110327933A

  • Methanol Synthesis.

    GB1159035A